A comparative study of the effect of institutional ownership, audit committee, and gender on audit report lag in Indonesia, Malaysia, and Singapore - Yulia Frischanita (STIE Perbanas Surabaya, 2018)
The purpose of this research are to analyst the negative effect of institutional ownership, audit committee and gender to audit report lag of mining company in Indonesia, Malaysia and Singapore for 2012-2016. Gender is proxied by gender of CEO and gender of Committee Audit’s Head. Not only that, the research also analyst the difference mean value of audit report lag in Indonesia, Malaysia and Singapore. This research use random purposive sampling technique because the amount company gap after purposive sampling between three counties are high. Total of population of three countries are 67 companies and mining company which fulfill the criteria of purposive sampling is 43 companies. That are consist of 34 Indonesia’s mining companies, 3 Malaysia’s mining companies and 6 Singapore’s mining companies. The final sample is 13 companies consist of 5 Indonesia’s company, 5 Singapore’s company and 3 Malaysia’s Company. Multiple Linear Regression is used to examine the effect of independent variable to dependent variable, while One Way-Anova is used to examine the difference mean value of audit report lag. The result of this research are institutional ownership have negative effect to audit report lag, while audit committee and gender don’t have effect to audit report lag. Beside that, there is no difference mean value of audit report lag in Indonesia, Malaysia and Singapore because they have same regulation about maximal day of company to publish their financial report.